Development and validation of a yoga module for adults with non-alcoholic fatty liver disease: a feasibility study - Mishra, Rakhi; Gupta, Rohit; Goyal, Bela; Bhadoria, Ajeet Singh; Kalyani, C. Vasantha; Sharma, Suresh K.; H. S., Vaidraj (International Journal Of Community Medicine And Public Health, 2025)
Background: Non-alcoholic fatty liver disease (NAFLD) is a prevailing disorder, increasing at an alarming rate. The existing literature lacks documentation regarding the validation of a specific yoga intervention tailored to meet the needs of individuals with NAFLD. The present study aims to develop and validate a yoga module for adults with NAFLD. Methods: The module included Joint loosening exercises (Neck, Shoulder, Knee, Trunk), Surya Namaskar, yoga postures (Asana-Ardha Matsyendrasana, Paschimottanasana, Naukasana), yogic breathing techniques (Pranayama- Surya Anuloma, Nadisodhana), and breathing relaxation practices were given for validation to 31 experts followed by a pilot trial on 12 adults with NAFLD. Results: Validation of the yoga module was done using item-level content validity index (I-CVI), scale-level content validity index using the average method (S-CVI), scale-level content validity index using the universal agreement method (S-CVI/UA), and the reliability score was 0.82, indicating the yoga module is reliable. The study found that 80% of adults with NAFLD accepted the selected yoga practices. Additionally, all adults with NAFLD (n=9) rated the intervention ≥3, indicating overall satisfaction and positive perception. There was significant improvement in controlled attenuation parameter (CAP) after 3 months of intervention. Conclusions: The newly developed yoga module for NAFLD was shown to be both feasible and beneficial for adult patients during the 3-month pilot trial.